2007
DOI: 10.1093/ps/86.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite Marker-Based Genetic Analysis of Relatedness Between Commercial and Heritage Turkeys (Meleagris gallopavo)

Abstract: The turkey is second only to the chicken in importance as an agriculturally important poultry species. Unlike the chicken, however, genetic studies of the turkey continue to be limited. For example, to date, many genomic investigations have been conducted to characterize genetic relationships between commercial (CO) and non-CO chicken breeds, whereas the nature of the genetic relatedness between CO and heritage turkeys remains unknown. The objective of the current research was to use microsatellites to analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 14 publications
2
17
0
1
Order By: Relevance
“…However, this was relatively low when compared to the generally reported number of alleles per locus for microsatellite loci in the literature, which usually ranged from two to more than 10, suggesting low levels of allelic diversity for the local populations of P. viridis. The MetaPhor ® agarose gels that we used to type the microsatellite loci in this study had been shown by Ochsenreither et al (2006) to be as efficient as polyacrylamide gels and an automated capillary sequencer system (CEQ 8000; Beckman Coulter, Fullerton, USA) and by Kamara et al (2007) to be comparable with the ABI PRISM 3100 Genetic Analyzer (Applied Biosystems, Foster City, USA) for microsatellite allele discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…However, this was relatively low when compared to the generally reported number of alleles per locus for microsatellite loci in the literature, which usually ranged from two to more than 10, suggesting low levels of allelic diversity for the local populations of P. viridis. The MetaPhor ® agarose gels that we used to type the microsatellite loci in this study had been shown by Ochsenreither et al (2006) to be as efficient as polyacrylamide gels and an automated capillary sequencer system (CEQ 8000; Beckman Coulter, Fullerton, USA) and by Kamara et al (2007) to be comparable with the ABI PRISM 3100 Genetic Analyzer (Applied Biosystems, Foster City, USA) for microsatellite allele discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…Higher number of alleles was observed using turkey microsatellites on the Roslin backcross families (Burt et al, 2003) and on commercial line (Reed et al, 2000(Reed et al, , 2002. In contrast, Kamara et al (2007) observed a low number of alleles in five heritage domestic populations using 10 polymorphic turkey microsatellites chosen from those identified by Burt et al (2003).…”
Section: Resultsmentioning
confidence: 84%
“…Microsatellites, also known as simple sequence repeats (SSRs), are highly polymorphic and abundant genetic markers (Li et al, 2002). They were widely employed in population genetic studies of numerous species, including poultry (Cheng and Crittenden, 1994;Kamara et al, 2007). Here, we developed and characterized 8 novel microsatellite markers for Huoyan geese, which will be useful for future studies on the population genetic structure and conservation genetics in this species.…”
Section: Introductionmentioning
confidence: 99%